Research and Application of Key Technologies for Refined Water Control in Digital Twin Irrigation Areas - LUO Zhaolin; MENG Qingkui; CHEN Wufen; ZHANG Bo (Renmin Zhujiang)
To improve the efficiency of water resource utilization in China and promote refined management of irrigation areas, this paper proposes a refined management framework for digital twin irrigation areas based on the current development of irrigation areas.Meanwhile, it studies the key technologies of water supply prediction in irrigation areas, crop water demand prediction, optimal water volume allocation in irrigation areas, and integrated measurement and control gates.A set of “FEDE” platforms for digital twin irrigation areas have been constructed, and five paths of “multi-factor three-dimensional perception”, “full-cycle water demand forecasting”, “targeted warning of drought and flood risks”, “full-process rehearsal of water resources”, and “scientific plans for disaster prevention and reduction” are adopted.As a result, comprehensive, intelligent, and scientific management of irrigation areas is realized.Additionally, some functions of the “FEDE” platform of digital twin irrigation areas have been successfully applied to the Liuxi River irrigation area, Guangzhou.The key technology of precise water volume control throughout the entire process of digital twin irrigation areas achieves optimal water resource allocation and improves water resource utilization efficiency by realizing water volume allocation throughout the entire “water supply-water demand-water distribution-water transfer” process.This has a guiding significance for the promotion and application of digital twin irrigation areas.